computer-assisted historical language comparison: an African linguistics perspective - (:unkn) unknown (My University, 2024)
This paper concerns the computational methodologies being adopted within the BANG project, and some preliminary results obtained. With data from Dogon languages, I first of all present data processing techniques being adopted and how these change the formats and nature of the data. I go on to detail some of the softwares and models being adopted and the preliminary results that these output. I conclude by showing various strategies that are being used for results visualization and modeling. The argument is that perfecting these techniques will lead to faster processing of data, so that much more attention can be given to tasks further upstream.
Keywords: African Research